CIC 822, 212 §3; CCEO 651, 15 §3 When Clerics and Bishops Clash over what Constitutes Appropriate Use of Social Media - Riley, Kenneth (2020)
Amplified in the world-wide COVID-19 pandemic, but already increasing year upon year, more and more attention by clergy is being marshalled to social media and blogging/Internet engagements. What canons and church teachings help us address growing disagreements between various clerics who are freely expressing their opinion on social media and web platforms vis-à-vis his Bishop’s role of vigilance?
Keywords: codex canonum ecclesiarum orientalium / 651